Risk Analysis of Equipment Loss During Marine Survey Operation by Integrating Fault Tree to Bayesian Network - Waskito, Dwitya Harits; Muhtadi, Ahmad; Prasetyo, Dimas Fajar; Kurniawan, Indra; Haryanto, Dwi; Riyadi, Adi Slamet (International Journal of Offshore and Coastal Engineering (IJOCE), 2024)
The process of deploying and towing the survey equipment for several marine survey activities is essential since it visualises the seabed and improves data accuracy. Since the equipment is deployed to an underwater level, the risk arises with the deployment. These risks include potential contact with submerged objects and the seabed, which can result in the loss of equipment and have detrimental environmental consequences. This study aims to analyse the risk-associated factors related to the loss of survey equipment using Fault Tree Analysis (FTA) and Bayesian Network (BN). The constructed FTA was converted into BN to find the relationship between Basic events and simulate the probability of updating Basic events. The sensitivity analysis results of the BN model indicate that "Procedure Failure" is the Basic contributor to the loss of survey equipment. The findings from this study will have practical implications for stakeholders, enabling them to enhance the safety of marine survey activities, particularly by mitigating the occurrence of equipment loss during operational procedures.